Environmental and Social Management System Implementation Handbook : Metal Products Manufacturing - International Finance Corporation (Washington, DC, 2015)
Environmental and social responsibility is becoming more and more important in today’s global economy. There are thousands of environmental and social codes and standards in the world today. The codes and standards define the rules and the objectives. But the challenge is in the implementation. An environmental and social management system (ESMS) helps companies to integrate the rules and objectives into core business operations, through a set of clearly defined, repeatable processes. This handbook is intended to be a practical guide to help companies develop and implement an (ESMS), which should help to improve overall operations. If a company has existing management systems for quality or health and safety, this handbook will help to expand them to include environmental and social performance.